Preparation method and application of collagen derivative and polysaccharide substance compounded self-gel hemostatic powder

The self-gelling powder, a composite of collagen derivatives and polysaccharides prepared by Schiff base reaction, solves the problems of postoperative adhesion and thrombosis caused by self-gelling powder residue, achieving rapid hemostasis and safe degradation, and is suitable for hemostasis of irregularly shaped wounds.

CN121015944APending Publication Date: 2025-11-28SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511211969.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-27
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing self-gelling powders tend to leave residues at wound sites, are difficult to remove, and can lead to postoperative adhesions and thrombosis. They also have a slow degradation rate and lack bioabsorbability.

Method used

A self-gelling hemostatic powder composed of collagen derivatives and polysaccharides was prepared by Schiff base reaction. It adheres to wound tissue through imine bonds and is hydrolyzed and dissociated after hemostasis is completed. It is then removed by body fluid degradation and metabolism to avoid residue.

Benefits of technology

It achieves rapid hemostasis, reduces the risk of postoperative adhesions and thrombosis, and the self-gelling powder is biocompatible in vitro and can be quickly removed in vivo, reducing the risk of immune rejection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121015944A_ABST
    Figure CN121015944A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of collagen derivative and polysaccharide substance compounded self-gel hemostatic powder, and relates to the field of biomedical materials. Aminated collagen derivatives and aldehyde polysaccharide substances are subjected to a Schiff base reaction through amino groups and aldehyde groups; further obtaining the Schiff base cross-linked aminated collagen derivative-aldehyde polysaccharide hydrogel, freeze-drying, and grinding into powder, so as to obtain the self-gel hemostatic powder. The self-gel hemostatic powder disclosed by the invention forms hydrogel in a wound tissue for adhesion and sealing, so that rapid hemostasis is realized, postoperative adhesion at the wound tissue is avoided, and healing of a wound is facilitated; after hemostasis is completed, the self-gel powder can be dissociated and removed from the tissue surface, and the risk that thrombus is formed and immunological rejection is caused is reduced; after hemostasis is completed, the hemostasis powder can be metabolized and absorbed by a human body along with thrombus, so that the residue of the hemostasis powder in the body is reduced, and the safety is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical materials, and in particular to a method for preparing a self-gelling hemostatic powder composed of collagen derivatives and polysaccharides, and its application. Background Technology

[0002] Excessive blood loss after trauma is a leading cause of traumatic death, accounting for 30-40% of all traumatic deaths. When blood loss reaches 20% of total blood volume within a short period, dizziness and other adverse effects may occur. If blood loss continues to exceed 40%, life is in danger. Bleeding from minor wounds can be stopped by the body's own physiological hemostatic mechanisms, but severe bleeding from serious trauma requires active human intervention to achieve effective hemostasis. Effective hemostasis techniques can significantly reduce death from excessive blood loss, thus prompting extensive research into hemostatic materials.

[0003] Ideal hemostatic materials should meet the following conditions: rapid blood coagulation, good adhesion and mechanical strength to seal the wound, and good biocompatibility. Various hemostatic materials have been developed to meet different application needs, including hemostatic gauze, hemostatic sponges, hemostatic hydrogels, and hemostatic powders. Despite the development of various hemostatic technologies and materials, rapid and effective hemostasis of bleeding from irregularly shaped, incompressible wounds remains a significant challenge. Among these, self-gelling powders have attracted widespread attention due to their wound shape adaptability and in-situ gelation to fill the wound, and are considered a good hemostatic material for irregularly shaped, incompressible wounds.

[0004] However, hemostatic powder materials are prone to residue and difficult to remove, which can lead to thrombosis and postoperative adhesions, hindering practical hemostatic applications. Therefore, developing a self-gelling hemostatic powder with good hemostatic effect, rapid removal after hemostasis, and reduced postoperative adhesions is of great significance for hemostasis of irregularly shaped, incompressible wounds (such as internal organs). Summary of the Invention

[0005] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is that existing self-gelling powders can cause abnormal adhesion between normal tissue and wound tissue, leading to postoperative adhesions; existing self-gelling powders are difficult to remove and easily remain at the wound site; existing self-gelling powders have a slow degradation rate or lack bioabsorbability.

[0006] To address the aforementioned technical problems, this invention designs and prepares a self-gelling hemostatic powder using collagen derivatives and polysaccharides as matrix materials to resist postoperative adhesion and rapid degradation. Compared to commercially available hemostatic powders, this self-gelling powder forms a hydrogel in wound tissue for adhesion and sealing. Simultaneously, the steric hindrance effect of the molecular chains on the hydrogel surface and the hydration layer prevent adhesion to normal tissue, reducing postoperative adhesion. In cases of internal bleeding such as visceral or vascular bleeding, it achieves rapid hemostasis while avoiding postoperative adhesion at the wound site, thus promoting wound healing.

[0007] The self-gel powder of this invention forms imine bonds through a Schiff base reaction, adhering to wound tissue. After hemostasis is achieved, the imine bonds hydrolyze, causing the powder to dissociate from the tissue surface and be degraded and metabolized by body fluids. This self-gel powder can be removed from the tissue surface after hemostasis, reducing the risk of thrombosis and immune rejection.

[0008] This invention uses collagen derivatives and polysaccharides as matrix materials to prepare self-gelling powder through Schiff base reaction. Under hydrolysis, enzymatic hydrolysis and other actions, it can be rapidly metabolized and absorbed by the human body. After hemostasis is completed, it can be metabolized and absorbed by the human body along with the thrombus, reducing the residue of hemostatic powder in the body and improving safety.

[0009] To achieve the above objectives, the present invention also provides a method for preparing a self-gelling hemostatic powder composed of collagen derivatives and polysaccharides, comprising the following steps: (1) Preparation of amino-modified collagen derivatives The collagen derivative was fully dissolved in PBS buffer solution, and diamine was added to the solution. The pH of the solution was adjusted to 5 using hydrochloric acid, and then a condensing agent was added as a reaction catalyst. The mixture was stirred continuously overnight at room temperature. After the reaction was completed, the reaction product was placed in pure water for dialyzing to remove unreacted diamine and condensing agent, and then freeze-dried to obtain the aminated collagen derivative. (2) Preparation of aldehyde-modified polysaccharides Polysaccharide, p-aldehyde benzoic acid, and a condensing agent were dissolved in dimethyl sulfoxide (DMSO) and reacted with stirring at room temperature for 18 hours. After the reaction, insoluble impurities were removed by filtration. The resulting product was precipitated in a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 9:1, and filtered to remove excess p-aldehyde benzoic acid, condensing agent, and dimethyl sulfoxide, yielding a white solid. The white solid was dissolved in DMSO, and precipitated again in the ethyl acetate-petroleum ether mixed solution, and filtered. This process was repeated three times to ensure complete removal of impurities. The white solid was then dissolved in deionized water, dialyzed for 48 hours, and freeze-dried to obtain the aldehyde-modified polysaccharide. (3) Preparation of self-gelling hemostatic powder Aminated collagen derivatives and aldehyde-modified polysaccharides were dissolved in deionized water at concentrations of 1-10 wt%, and the two solutions were mixed evenly at different mass ratios. After standing, the amino and aldehyde groups underwent a Schiff base reaction to obtain a Schiff base cross-linked aminated collagen derivative-aldehyde-modified polysaccharide hydrogel. The hydrogel was freeze-dried and ground into powder to obtain a self-gelling hemostatic powder.

[0010] Preferably, the collagen derivative mentioned in step (1) is selected from any one or more of gelatin, aminogelatin, carboxylated gelatin, methacrylamide gelatin, alkylated gelatin, and collagen.

[0011] Preferably, the diamine in step (1) is selected from one or more of ethylenediamine, propylenediamine, butanediamine, pentanediamine, and hexanediamine.

[0012] Preferably, the polysaccharide in step (2) is selected from one or more of dextran, chitosan, hyaluronic acid, sodium alginate, and cellulose.

[0013] Preferably, the condensing agent in steps (1) and (2) is selected from one or more of EDCI, NHS, DMAP, Hobt and DCC.

[0014] Preferably, the dialysis bag used in steps (1) and (2) has a molecular weight cutoff of 1-140 kDa.

[0015] Preferably, the grinding method in step (3) is selected from one or more of the following: manual grinding, ball milling, vibration milling, air jet milling, stirring milling, and cryogenic grinding.

[0016] Preferably, the particle size of the self-gelling hemostatic powder obtained by grinding in step (3) is 1-100µm.

[0017] Further, the concentration of the collagen derivative solution in step (1) is 0.1-100 mg / mL.

[0018] Furthermore, the molar ratio of the collagen derivative to the added diamine in step (1) is 0.1-10:1.

[0019] Furthermore, the molar ratio of collagen derivative to condensing agent in step (1) is 0.1-10:1.

[0020] Furthermore, the concentration of the polysaccharide solution in step (2) is 0.1-100 mg / mL.

[0021] Furthermore, the molecular weight of the polysaccharide in step (2) is 1.5-1500 kDa.

[0022] Furthermore, the molar ratio of polysaccharide to condensing agent in step (2) is 0.1-10:1.

[0023] Furthermore, the molar ratio of the polysaccharide and p-aldehyde benzoic acid mentioned in step (2) is 0.1-10:1.

[0024] Furthermore, the mass ratio of the amino-modified collagen derivative to the aldehyde-modified polysaccharide in step (3) is 0.1-10:1.

[0025] The present invention also provides a self-gelling hemostatic powder obtained by the above method, and the application of the hemostatic powder in the preparation of hemostatic materials or wound dressings.

[0026] The self-gelling hemostatic powder prepared by the method of the present invention comprises collagen derivative material, polysaccharide macromolecule material, diamine substance, and p-aldehyde benzoic acid. The diamine substance is grafted onto the collagen derivative backbone, and the p-aldehyde benzoic acid is grafted onto the polysaccharide macromolecule backbone. Furthermore, the amino-modified collagen derivative and the aldehyde-modified polysaccharide macromolecule are cross-linked with each other.

[0027] Technical effect

[0028] This invention designs and prepares a self-gelling hemostatic powder using collagen derivatives and polysaccharides as matrix materials, which resists postoperative adhesion and rapidly degrades. Compared to commercially available hemostatic powders, this invention exhibits superior postoperative anti-adhesion properties. While forming adhesion and sealing to the wound, it also creates a hydration layer with strong steric hindrance, providing lubrication, reducing adhesion to normal tissue, and preventing postoperative adhesion. This invention also possesses excellent shape adaptability, capable of adapting to and filling wounds of different shapes, preventing blood loss. Furthermore, this invention exhibits good biodegradability and bioabsorbability, allowing for rapid degradation and metabolism by the body after hemostasis, avoiding residue problems in the body and reducing the risks of thrombosis and immune rejection. This invention provides a safe and effective hemostatic method for bleeding from irregularly shaped, incompressible wounds within the body.

[0029] The self-gelling hemostatic powder of this invention possesses excellent adhesive mechanical properties, in vitro coagulation properties, and biocompatibility. Compared with commercial chitosan hemostatic powder, this invention exhibits significant advantages in adhesive performance, providing a stronger wound sealing effect. Wounds treated with this self-gelling hemostatic powder show virtually no postoperative adhesion and do not affect wound healing.

[0030] This invention provides a self-gelling hemostatic powder obtained by blending collagen derivatives and polysaccharides after simple chemical modification, based on a Schiff base reaction. The matrix materials constituting the self-gelling hemostatic powder—collagen derivatives and polysaccharides—are commonly used biomolecular materials with wide availability and mature production methods, allowing for low-cost raw material acquisition in actual production. The chemical modification methods for collagen derivatives and polysaccharides are simple, requiring no special reaction conditions or environments, and possess the potential for large-scale industrial production.

[0031] This invention provides a good hemostasis solution for bleeding from irregularly shaped and incompressible wounds in the body. While ensuring hemostasis, it avoids the defects of existing hemostatic powders and has broad application prospects and transformation potential. It is expected to provide an ideal solution for application needs such as acute bleeding caused by trauma and internal bleeding caused by surgery. Attached Figure Description

[0032] The following will further explain the concept, specific structure, and technical effects of the present invention in conjunction with the accompanying drawings, so as to fully understand the purpose, features, and effects of the present invention.

[0033] Figure 1 This is a schematic diagram illustrating the preparation and usage methods according to an embodiment of the present invention; Figure 2 These are the adhesion performance data of the anti-adhesion self-gelling powder of the present invention on the surface of pigskin; Figure 3 These are the burst strength data of the anti-adhesion self-gelling powder of the present invention on the surface of pigskin; Figure 4 This is an in vitro coagulation experiment of the anti-adhesion self-gelling powder of the present invention; Figure 5 These are the in vitro coagulation index data of the anti-adhesion self-gelling powder of the present invention; Figure 6 This refers to the hemolysis rate data of the anti-adhesion self-gelling powder of the present invention; Figure 7 and Figure 8 These are the cytotoxicity test data of the anti-adhesion self-gelling powder of the present invention; Figure 9 These are the in vitro degradation rate data of the anti-adhesion self-gelling powder of the present invention; Figure 10 This is a schematic diagram of hemostasis in the rat liver hemorrhage model of the present invention; Figure 11 These are hemostasis time data of a rat liver hemorrhage model using the anti-adhesion self-gelling powder of the present invention; Figure 12This is the blood loss data of the rat liver hemorrhage model using the anti-adhesion self-gelling powder of the present invention; Figure 13 These are experimental data on rat liver wound healing and anti-postoperative adhesion of the anti-adhesion self-gelling powder of the present invention. Detailed Implementation

[0034] The following description, with reference to the accompanying drawings, illustrates several preferred embodiments of the present invention to make its technical content clearer and easier to understand. The present invention can be embodied in many different forms, and the scope of protection of the present invention is not limited to the embodiments mentioned herein.

[0035] Figure 1 This is a schematic diagram illustrating the preparation and usage methods of an embodiment of the present invention. The technical principle of the present invention is to prepare a self-gel powder by simple chemical modification of collagen derivatives and polysaccharides and cross-linking them under a Schiff base reaction. The present invention possesses excellent adhesion, coagulation, and biocompatibility. Upon contact with a wound, it adheres to and seals the wound through a Schiff base reaction, achieving rapid hemostasis. After hemostasis is achieved, the present invention provides a lubricating effect through the steric hindrance effect and hydration layer on the surface, preventing postoperative adhesions and promoting wound healing. The present invention also exhibits good biodegradability and bioabsorbability, allowing for rapid metabolism and absorption by the human body, reducing residues in the body, and demonstrating a high level of safety.

[0036] Example 1

[0037] 5 g of gelatin was dissolved thoroughly in 100 ml of PBS buffer solution, and 0.24 mol of ethylenediamine (EDA) was added to the solution. The pH of the solution was adjusted to 5 using hydrochloric acid, and then 0.012 mol of carbodiimide hydrochloride (EDCI) was added as a reaction catalyst. The mixture was stirred continuously overnight at room temperature. After the reaction was completed, the reaction product was dialyzed in pure water to remove unreacted ethylenediamine and EDCI, and then freeze-dried to obtain aminated gelatin.

[0038] Example 2

[0039] 5 g of collagen was dissolved in 100 ml of PBS buffer, and 0.24 mol of ethylenediamine (EDA) was added to the solution. The pH of the solution was adjusted to 5 using hydrochloric acid, and then 0.012 mol of carbodiimide hydrochloride (EDCI) was added as a reaction catalyst. The mixture was stirred continuously overnight at room temperature. After the reaction was completed, the reaction product was dialyzed in pure water to remove unreacted ethylenediamine and EDCI, and then freeze-dried to obtain aminated collagen.

[0040] Example 3

[0041] 2 g of dextran, 0.96 g of p-aldehyde benzoic acid, and 0.12 g of 4-dimethylaminopyridine (DMAP) were dissolved in 20 mL of dimethyl sulfoxide (DMSO), followed by the addition of 1.2 g of dicyclohexylcarbodiimide (DCC). The mixture was stirred at room temperature for 18 hours. After the reaction was complete, insoluble impurities were removed by filtration. The resulting product was precipitated in a 9:1 volume ratio of ethyl acetate and petroleum ether, and filtered to remove excess p-aldehyde benzoic acid, catalyst, and dimethyl sulfoxide, yielding a white solid. The white solid was dissolved in DMSO, and precipitated again in the ethyl acetate-petroleum ether mixture, and filtered. This process was repeated three times to ensure complete removal of impurities. The white solid was dissolved in deionized water, dialyzed for 48 hours, and then freeze-dried to obtain aldehyde-modified dextran.

[0042] Example 4

[0043] 2 g of sodium alginate, 0.96 g of p-aldehyde benzoic acid, and 0.12 g of 4-dimethylaminopyridine (DMAP) were dissolved in 20 ml of dimethyl sulfoxide (DMSO), followed by the addition of 1.2 g of dicyclohexylcarbodiimide (DCC). The mixture was stirred at room temperature for 18 hours. After the reaction was complete, insoluble impurities were removed by filtration. The resulting product was precipitated in a 9:1 volume ratio of ethyl acetate and petroleum ether, and filtered to remove excess p-aldehyde benzoic acid, catalyst, and dimethyl sulfoxide, yielding a white solid. The white solid was dissolved in DMSO, and precipitated again in the ethyl acetate-petroleum ether mixture, and filtered. This process was repeated three times to ensure complete removal of impurities. The white solid was dissolved in deionized water, dialyzed for 48 hours, and then freeze-dried to obtain aldehyde-modified sodium alginate.

[0044] Example 5

[0045] 2 g of chitosan, 0.96 g of p-aldehyde benzoic acid, and 0.12 g of 4-dimethylaminopyridine (DMAP) were dissolved in 20 mL of dimethyl sulfoxide (DMSO). Then, 1.2 g of dicyclohexylcarbodiimide (DCC) was added, and the mixture was stirred at room temperature for 18 hours. After the reaction, insoluble impurities were removed by filtration. The resulting product was precipitated in a 9:1 volume ratio of ethyl acetate and petroleum ether, filtered, and excess p-aldehyde benzoic acid, catalyst, and dimethyl sulfoxide were removed, yielding a white solid. The white solid was dissolved in DMSO, precipitated again in the ethyl acetate-petroleum ether mixture, and filtered. This process was repeated three times to ensure complete removal of impurities. The white solid was dissolved in deionized water, dialyzed for 48 hours, and then freeze-dried to obtain aldehyde-modified chitosan.

[0046] Example 6

[0047] 2 g of hyaluronic acid, 0.96 g of p-aldehyde benzoic acid, and 0.12 g of 4-dimethylaminopyridine (DMAP) were dissolved in 20 ml of dimethyl sulfoxide (DMSO), followed by the addition of 1.2 g of dicyclohexylcarbodiimide (DCC). The mixture was stirred at room temperature for 18 hours. After the reaction was complete, insoluble impurities were removed by filtration. The resulting product was precipitated in a 9:1 volume ratio of ethyl acetate and petroleum ether, and filtered to remove excess p-aldehyde benzoic acid, catalyst, and dimethyl sulfoxide, yielding a white solid. The white solid was dissolved in DMSO, and precipitated again in the ethyl acetate-petroleum ether mixture, and filtered. This process was repeated three times to ensure complete removal of impurities. The white solid was dissolved in deionized water, dialyzed for 48 hours, and then freeze-dried to obtain aldehyde-modified hyaluronic acid.

[0048] Example 7

[0049] Aminated gelatin and aldehyde-modified dextran were dissolved in deionized water at a concentration of 10 wt%, and the two solutions were mixed at different mass ratios and vortexed for 5 seconds to ensure homogeneity. After standing, a Schiff base reaction occurred between the amino and aldehyde groups, resulting in a Schiff base-crosslinked aminated gelatin-aldehyde-modified dextran hydrogel. The hydrogel was freeze-dried and ground into powder to obtain a self-gelling hemostatic powder.

[0050] Example 8

[0051] Aminated gelatin and aldehyde-modified dextran were dissolved separately in deionized water at a concentration of 5 wt%. The two solutions were then mixed at different mass ratios and vortexed for 5 seconds to ensure homogeneity. After standing, a Schiff base reaction occurred between the amino and aldehyde groups, resulting in a Schiff base-crosslinked aminated gelatin-aldehyde-modified dextran hydrogel. The hydrogel was freeze-dried and ground into powder to obtain a self-gelling hemostatic powder.

[0052] Example 9

[0053] Aminated collagen and aldehyde-modified dextran were dissolved in deionized water at a concentration of 10 wt%, and the two solutions were mixed at different mass ratios and vortexed for 5 seconds to ensure homogeneity. After standing, a Schiff base reaction occurred between the amino and aldehyde groups, resulting in a Schiff base-crosslinked aminated collagen-aldehyde-modified dextran hydrogel. The hydrogel was freeze-dried and ground into powder to obtain a self-gelling hemostatic powder.

[0054] Example 10

[0055] Aminated gelatin and aldehyde-modified hyaluronic acid were dissolved in deionized water at a concentration of 10 wt%, and the two solutions were mixed at different mass ratios and vortexed for 5 seconds to ensure homogeneity. After standing, a Schiff base reaction occurred between the amino and aldehyde groups, resulting in a Schiff base-crosslinked aminated gelatin-aldehyde-modified hyaluronic acid hydrogel. The hydrogel was freeze-dried and ground into powder to obtain a self-gelling hemostatic powder.

[0056] Example 11

[0057] Aminated collagen and aldehyde-modified hyaluronic acid were dissolved separately in deionized water at a concentration of 10 wt%. The two solutions were then mixed at different mass ratios and vortexed for 5 seconds to ensure homogeneity. After standing, a Schiff base reaction occurred between the amino and aldehyde groups, resulting in a Schiff base-crosslinked aminated collagen-aldehyde-modified hyaluronic acid hydrogel. The hydrogel was freeze-dried and ground into powder to obtain a self-gelling hemostatic powder.

[0058] Example 12

[0059] Aminated gelatin and aldehyde-modified sodium alginate were dissolved in deionized water at a concentration of 10 wt%. The two solutions were then mixed at different mass ratios and vortexed for 5 seconds to ensure homogeneity. After standing, a Schiff base reaction occurred between the amino and aldehyde groups, resulting in a Schiff base crosslinked aminated gelatin-aldehyde-modified sodium alginate hydrogel. The hydrogel was freeze-dried and ground into powder to obtain a self-gelling hemostatic powder.

[0060] Example 13

[0061] Aminated gelatin and aldehyde-modified chitosan were dissolved in deionized water at a concentration of 10 wt%, and the two solutions were mixed at different mass ratios and vortexed for 5 seconds to ensure homogeneity. After standing, a Schiff base reaction occurred between the amino and aldehyde groups, resulting in a Schiff base-crosslinked aminated gelatin-aldehyde-modified chitosan hydrogel. The hydrogel was freeze-dried and ground into powder to obtain a self-gelling hemostatic powder.

[0062] Example 14

[0063] Aminated collagen and aldehyde-modified sodium alginate were dissolved separately in deionized water at a concentration of 10 wt%. The two solutions were then mixed at different mass ratios and vortexed for 5 seconds to ensure homogeneity. After standing, a Schiff base reaction occurred between the amino and aldehyde groups, resulting in a Schiff base-crosslinked aminated collagen-aldehyde-modified sodium alginate hydrogel. The hydrogel was freeze-dried and ground into powder to obtain a self-gelling hemostatic powder.

[0064] Example 15

[0065] Aminated collagen and aldehyde-modified chitosan were dissolved separately in deionized water at a concentration of 10 wt%. The two solutions were then mixed at different mass ratios and vortexed for 5 seconds to ensure homogeneity. After standing, a Schiff base reaction occurred between the amino and aldehyde groups, resulting in a Schiff base-crosslinked aminated collagen-aldehyde-modified chitosan hydrogel. The hydrogel was freeze-dried and ground into powder to obtain a self-gelling hemostatic powder.

[0066] Example 16

[0067] Pigskin was fixed in a cylindrical mold, and puncture defects were created on the pigskin using a custom-made 2 mm diameter circular cutter. The cylindrical mold was connected to an injection pump and a pressure monitor via a three-way pump, and the entire device was filled with PBS buffer solution. 100 μl of blood was dropped onto the surface of the pigskin, and appropriate amounts of the anti-adhesion self-gelling powder prepared in Example 7 or commercial chitosan hemostatic powder were added to form a blood gel, which was then allowed to stand for 5 minutes. Subsequently, the pump was moved at a rate of 2 ml / min to inject PBS, while the morphology of the blood clot and the pressure reading of the pressure monitor were observed. The pressure at which the pressure monitor began to drop was considered the burst pressure. Figure 3 The data shows the burst strength of the anti-adhesion self-gelling powder of the present invention on the surface of pigskin. The results show that the blood gel formed by the anti-adhesion self-gelling powder of the present invention on the surface of pigskin can withstand a burst pressure of 89.2 mm Hg, while the commercial chitosan hemostatic powder can only withstand a burst pressure of 19.4 mm Hg.

[0068] Example 17

[0069] Pigskin measuring 6 cm × 1 cm was prepared, with an adhesive area of ​​1 cm × 1 cm. It was stretched at 50 mm / min. A gel was formed by applying 50 μl of blood to the pigskin and adding 10 mg of the anti-adhesion self-gelling powder prepared in Example 7 or commercial chitosan hemostatic powder. A 200 g weight was applied for 5 seconds, and the gel was incubated at 37°C for 1 hour. The shear strength was determined by dividing the maximum force by the adhesive area. Figure 2 The data show the adhesion performance of the anti-adhesion self-gelling powder of the present invention on the surface of pigskin. The results show that the adhesion formed by the anti-adhesion self-gelling powder of the present invention on the surface of pigskin has an average shear strength of 2.13 kPa, while the adhesion of commercial chitosan hemostatic powder on the surface of pigskin has a shear strength of only 1.01 kPa.

[0070] Example 18

[0071] Ten mg of the anti-adhesion self-gelling powder prepared in Example 7 or commercial chitosan hemostatic powder were added to the sequential wells of a 96-well plate containing 50 μl of blood. Each well was gently washed with 1 ml of physiological saline at time points of 15, 30, 45, and 60 seconds to completely remove any uncoagulated blood components. After washing, the morphology of the blood clot in the 96-well plate was photographed and observed. The time it took for a uniform and stable clot to form in the well after washing was defined as the clotting time. Figure 4 The in vitro coagulation experiment of the anti-adhesion self-gelling powder of the present invention showed that the anti-adhesion self-gelling powder achieved stable coagulation within 15 seconds, while commercial chitosan hemostatic powder only achieved partial coagulation after 45 seconds.

[0072] Example 19

[0073] Physiological saline collected from the blood gel washing at different time points in Example 18 was collected, and 100 µl of each was added to a 96-well plate. The in vitro coagulation index (BCI) was measured using an ELISA reader. The lower the BCI, the better the coagulation effect. Figure 5 The in vitro coagulation index data of the anti-adhesion self-gel powder of the present invention shows that the anti-adhesion self-gel powder exhibits excellent coagulation performance within 15 seconds with a coagulation index of 0.40%, while the commercial chitosan hemostatic powder still has a coagulation index of 19.47% after 45 seconds of coagulation.

[0074] Example 20

[0075] Whole blood was centrifuged at 200×g for 10 minutes, washed with physiological saline, and centrifuged again. This process was repeated three times to obtain concentrated red blood cells. 50µl of concentrated red blood cells were added to each 1 ml of physiological saline to obtain a 5% (V / V) red blood cell dilution. Simultaneously, 10 mg of hemostatic powder was added to each 1 ml of physiological saline to prepare a 10 mg / ml hemostatic powder solution.

[0076] Mix 0.8 ml of hemostatic powder solution with 0.2 ml of erythrocyte diluent. Similarly, mix 0.8 ml of physiological saline and 0.1% Triton X-100 solution as negative and positive controls, respectively, with 0.2 ml of erythrocyte diluent. Incubate the mixture at 37°C for 24 hours. After incubation, centrifuge the erythrocyte suspension at 500×g for 15 minutes, add the supernatant to a 96-well plate, and read the absorbance at 540 nm using a microplate reader to assess the degree of erythrocyte damage. Figure 6 This data shows the hemolysis rate of the anti-adhesion self-gelling powder of the present invention. A hemolysis rate of less than 5% is considered to indicate a high level of safety for the hemostatic material. Experimental results show that the hemolysis rate of the anti-adhesion self-gelling powder is only 1.02%.

[0077] Example 21

[0078] Cell viability was assessed using MTS staining. 10,000 human umbilical vein endothelial cells (Huevc) were seeded in each well of a 96-well plate and incubated for 12 hours at 37°C with 100 µl of DMEM complete medium in 5% CO2 to allow complete cell adhesion. The culture medium was then aspirated, and medium containing hemostatic powder at concentrations of 10 mg / ml, 5 mg / ml, 2.5 mg / ml, 1 mg / ml, and 0.5 mg / ml were added, respectively, and incubation continued for 24 hours. Medium without hemostatic powder was used as a negative control. After 24 hours of incubation, 10 µl of MTS reagent was added to each well for staining, and the absorbance at 490 nm was measured using a microplate reader. Figure 7 and Figure 8 The data presented are cytotoxicity test data of the anti-adhesion self-gelling powder of the present invention. The experimental results show that the cell viability incubated with different concentrations of anti-adhesion self-gelling powder solution did not show a significant decrease compared with the control group, indicating that the present invention has low cytotoxicity.

[0079] Example 22

[0080] Cell viability was assessed using a live-dead cell staining method. 10,000 human umbilical vein endothelial cells (Huevc) were seeded in each well of a 96-well plate and incubated for 12 hours at 37°C with 10 µl of DMEM complete medium to allow complete cell adhesion. The culture medium was then aspirated, and medium containing 10 mg / ml, 5 mg / ml, 2.5 mg / ml, 1 mg / ml, and 0.5 mg / ml hemostatic powder, respectively, were added, followed by incubation for another 24 hours. Medium without hemostatic powder was used as a negative control. Afterward, the medium was removed, and the cells were washed at least three times with PBS. Each well was stained using a Calcein-AM / PI cell double staining kit, and observed under a fluorescence microscope. Figure 7 and Figure 8 The data presented are cytotoxicity test results of the anti-adhesion self-gelling powder of the present invention. Fluorescence microscopy observation results show that no abnormal cell death occurred in the cells incubated with the self-gelling powder, and all cells survived normally, indicating that the present invention has low cytotoxicity.

[0081] Example 23

[0082] Take 100 µl of blood and add 20 mg of the anti-adhesion self-gelling powder prepared in Example 7 or commercial chitosan hemostatic powder to absorb the blood and form a blood clot. Let the blood clot stand for 60 minutes to allow it to stabilize. Place the blood clot in PBS buffer (pH=7.4) containing lysozyme and amylase (0.2 mg / ml each) and incubate at 37°C.

[0083] The solution was centrifuged daily, the supernatant was removed, and a fresh enzyme solution was added. At the set time points, the solution was centrifuged (200×g, 10 min), the supernatant was removed, and the solution was lyophilized. The remaining mass of the blood clot was weighed, and the in vitro degradation rate was measured using the rate of mass loss. Figure 9 The data on the in vitro degradation rate of the anti-adhesion self-gel powder of the present invention shows that the blood clot formed by the anti-adhesion self-gel powder and blood can be basically degraded within 14 days, while the blood clot formed by commercial chitosan hemostatic powder and blood still has a remaining mass of 60.7% after 14 days.

[0084] Example 24

[0085] The overall hemostatic performance of the hemostatic powder was evaluated using a rat liver hemorrhage model. A 6 mm diameter, 2 mm deep lesion was created in the rat liver using a biopsy puncture device, and the hemostatic material was immediately applied to the bleeding site. The hemostasis time and blood loss in the rat liver were recorded.

[0086] Figure 10 This is a schematic diagram of hemostasis in the rat liver hemorrhage model of the present invention. Figure 11 These are hemostasis time data from a rat liver hemorrhage model using the anti-adhesion self-gelling powder of this invention. Figure 12 This paper presents blood loss data in a rat liver hemorrhage model using the anti-adhesion self-gelling powder of this invention. Experimental results show that the average hemostasis time for rat livers without any hemostatic material was 533.21 seconds, with a blood loss of 6.10 g; the average hemostasis time for rat livers with commercial chitosan hemostatic powder was 234.33 seconds, with a blood loss of 2.05 g; while the average hemostasis time for rat livers using the anti-adhesion self-gelling powder was 120.67 seconds, with a blood loss of only 0.46 g. Compared to commercial chitosan hemostatic powder, the anti-adhesion self-gelling powder exhibits shorter hemostasis time and significantly less blood loss, demonstrating excellent hemostatic effects in the rat liver hemorrhage model.

[0087] Example 25

[0088] The hemostatic material from Example 24 was retained at the liver wound of rats. The liver with the implant was removed after anesthesia on the 3rd, 7th and 14th days after implantation of the hemostatic material. The liver was fixed in 4% paraformaldehyde for 24 hours, embedded in paraffin, and stained with HE and Masson staining. The liver was then observed under a microscope.

[0089] Figure 13 The data presented are experimental data on rat liver wound healing and anti-postoperative adhesion of the anti-adhesion self-gelling powder of the present invention. The experimental results show that a large amount of hemostatic powder remains at the wound after treatment with commercial chitosan hemostatic powder, and no obvious degradation occurs over time, leading to significant postoperative adhesion and lesions in the liver, which affects the normal healing of liver wounds.

[0090] Due to the steric hindrance effect and hydration layer on the hydrogel surface formed by the anti-adhesion self-gel powder, it acts as a barrier and lubricating layer, reducing tissue adhesion. Therefore, no significant postoperative adhesions appeared at the wound site treated with the anti-adhesion self-gel powder. Furthermore, over time, the hydrogel on the wound surface dissociates and degrades, allowing the liver wound to heal normally. This indicates that the anti-adhesion self-gel powder has excellent anti-postoperative adhesion properties, forming a seal and adhesion around the wound while reducing postoperative adhesions, thus promoting wound tissue healing and recovery.

[0091] This invention designs and prepares a self-gelling hemostatic powder using collagen derivatives and polysaccharides as matrix materials, which resists postoperative adhesion and rapidly degrades. Compared to commercially available hemostatic powders, this invention exhibits superior postoperative anti-adhesion properties. While forming adhesion and sealing to the wound, it also creates a hydration layer with strong steric hindrance, providing lubrication, reducing adhesion to normal tissue, and preventing postoperative adhesion. This invention also possesses excellent shape adaptability, capable of adapting to and filling wounds of different shapes, preventing blood loss. Furthermore, this invention exhibits good biodegradability and bioabsorbability, allowing for rapid degradation and metabolism by the body after hemostasis, avoiding residues of hemostatic materials in the body and reducing the risks of thrombosis and immune rejection. In summary, this invention provides a safe and effective hemostatic method for bleeding from irregularly shaped, incompressible wounds within the body.

[0092] This invention exhibits excellent adhesive mechanical properties, in vitro coagulation properties, and biocompatibility. Compared to commercial chitosan hemostatic powder, this invention demonstrates a significant advantage in adhesive properties, providing a stronger wound sealing effect. In in vitro coagulation performance, this invention achieves rapid coagulation within 15 seconds, exhibiting a faster in vitro coagulation rate and effect compared to commercial chitosan hemostatic powder. Regarding biocompatibility, this invention exhibits low cytotoxicity, low hemolysis, and rapid biodegradability, demonstrating a good safety level. In a rat liver hemorrhage model, this invention demonstrates excellent hemostatic effect within 2 minutes, significantly superior to the 4-minute hemostatic effect of commercial chitosan hemostatic powder; in terms of blood loss, due to the good shape adaptability of this invention, it fills and seals the wound, resulting in less than 0.5 g of blood loss. In a rat liver wound healing model, wounds treated with this invention showed virtually no postoperative adhesions, while wounds treated with commercial chitosan hemostatic powder exhibited significant postoperative adhesions, severely affecting wound healing.

[0093] This invention provides a self-gelling hemostatic powder by simply chemically modifying collagen derivatives and polysaccharides and then blending them under a Schiff base reaction. The matrix materials constituting the self-gelling hemostatic powder—collagen derivatives and polysaccharides—are commonly used biomolecular materials with wide availability and mature production methods, allowing for low-cost raw material acquisition in actual production. The chemical modification methods for collagen derivatives and polysaccharides are simple, requiring no special reaction conditions or environments, and possess the potential for large-scale industrial production. This invention provides an excellent hemostatic solution for bleeding from irregularly shaped, incompressible wounds in vivo, ensuring hemostatic efficacy while avoiding the shortcomings of existing hemostatic powders. It has broad application prospects and transformation potential, and is expected to provide an ideal solution for applications such as acute bleeding caused by trauma and internal bleeding during surgery.

[0094] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.

Claims

1. A method for preparing a self-gelling hemostatic powder composed of collagen derivatives and polysaccharides, characterized in that, It includes the following steps: (1) Preparation of amino-modified collagen derivatives Collagen derivatives were fully dissolved in PBS buffer solution, and diamine was added to the solution. The pH of the solution was adjusted to 5 using hydrochloric acid, and then a condensing agent was added as a reaction catalyst. After stirring continuously overnight at room temperature, the reaction product was placed in pure water for dialysis to remove unreacted diamine and condensing agent, and then freeze-dried to obtain amino-modified collagen derivatives. (2) Preparation of aldehyde-modified polysaccharide substances Polysaccharide, p-aldehyde benzoic acid, and condensing agent were dissolved in dimethyl sulfoxide (DMSO) and stirred at room temperature for 18 hours. After the reaction, insoluble impurities were removed by filtration. The resulting product was precipitated in a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 9:1, filtered, and excess p-aldehyde benzoic acid, condensing agent, and dimethyl sulfoxide were removed to obtain a white solid. The white solid was dissolved in DMSO, precipitated again in the ethyl acetate and petroleum ether mixed solution, and filtered. This process was repeated three times to ensure complete removal of impurities. The white solid was dissolved in deionized water, dialyzed for 48 hours, and then freeze-dried to obtain the aldehyde-modified polysaccharide. (3) Preparation of self-gelling hemostatic powder Aminated collagen derivatives and aldehyde-modified polysaccharides were dissolved in deionized water at concentrations of 1-10 wt%, and the two solutions were mixed evenly at different mass ratios. After standing, the amino and aldehyde groups underwent a Schiff base reaction to obtain a Schiff base cross-linked aminated collagen derivative-aldehyde-modified polysaccharide hydrogel. The hydrogel was freeze-dried and ground into powder to obtain a self-gelling hemostatic powder.

2. The method for preparing a self-gelling hemostatic powder composed of collagen derivatives and polysaccharides according to claim 1, characterized in that, The collagen derivative mentioned in step (1) is selected from any one or more of gelatin, aminogelatin, carboxylated gelatin, methacrylamide gelatin, alkylated gelatin, and collagen; the diamine is selected from one or more of ethylenediamine, propylenediamine, butanediamine, pentanediamine, and hexamethylenediamine.

3. The method for preparing a self-gelling hemostatic powder composed of collagen derivatives and polysaccharides according to claim 1, characterized in that, The condensing agent in steps (1) and (2) is selected from one or more of EDCI, NHS, DMAP, Hobt and DCC.

4. The method for preparing a self-gelling hemostatic powder composed of collagen derivatives and polysaccharides according to claim 1, characterized in that, In step (1), the molar ratio of collagen derivative to ethylenediamine (EDA) is 0.1-10:1, and the molar ratio of collagen derivative to condensing agent is 0.1-10:

1.

5. The method for preparing a self-gelling hemostatic powder composed of collagen derivatives and polysaccharides according to claim 1, characterized in that, The polysaccharide mentioned in step (2) is selected from one or more of dextran, chitosan, hyaluronic acid, sodium alginate, and cellulose.

6. The method for preparing a self-gelling hemostatic powder composed of collagen derivatives and polysaccharides according to claim 1, characterized in that, The molar ratio of polysaccharide to p-aldehyde benzoic acid in step (2) is 0.1-10:1, and the molar ratio of polysaccharide to condensing agent is 0.1-10:

1.

7. The method for preparing a self-gelling hemostatic powder composed of collagen derivatives and polysaccharides according to claim 1, characterized in that, The mass ratio of the amino-modified collagen derivative and the aldehyde-modified polysaccharide mentioned in step (3) is 0.1-10:

1.

8. The method for preparing a self-gelling hemostatic powder composed of collagen derivatives and polysaccharides according to claim 1, characterized in that, In step (3), the grinding method is selected from one or more of the following: manual grinding, ball milling, vibration milling, air jet milling, stirring milling, and cryogenic grinding.

9. The collagen derivative and polysaccharide self-gelling hemostatic powder obtained by the preparation method according to any one of claims 1 to 8.

10. The application of the collagen derivative and polysaccharide self-gelling hemostatic powder according to claim 9 in the preparation of hemostatic materials or wound dressings.

Citation Information

Cited By

  • Adhesive styptic powder and preparation method thereof

    CN121927108A